Development and validation of an analytical method for detecting chlorantraniliprole residues in fresh tea leaves - Tengfei Liu; Minghui Dong; Fengjie Zhou; Daifeng Yang; Xueming Zhang (Food Science and Human Wellness)
An efficient method using multiwalled carbon nanotubes (MWCNTs) as dispersive solid-phase extraction sorbent was established for determining chlorantraniliprole residues in fresh tea leaves, which are known to be a troublesome matrix containing abundant pigments, via gas chromatography with an electron capture detector. Acetonitrile was used as the extraction solvent, with sodium chloride enhancing the analyte partition in the organic phase. The optimal mixture of MWCNTs and primary secondary amine (PSA) was based on the distribution of the target analyte recovery and on the clean-up efficiency; while matrix-matched calibration was recommended to combat the matrix effect. Mean recoveries of 95.2%–108.8% were obtained with intraday and interday precisions of less than 7.9% and 10.3%, respectively. Good linearity was observed for concentrations of 0.02–1.0 mg/kg with a correlation coefficient of 0.9984. The limits of detection and quantification were 0.005 mg/kg and 0.02 mg/kg, respectively. The method was employed to investigate the dissipation dynamics of chlorantraniliprole in fresh tea leaves with real field samples. Consequently, the dissipation rates of chlorantraniliprole in fresh tea leaves followed pseudo-first-order kinetics with a half-life of 1.9 d, and the average chlorantraniliprole residue content was below 0.02 mg/kg with a harvest withholding period of 14 d. Keywords: Multiwalled carbon nanotubes, Fresh tea leaves, Chlorantraniliprole, Dispersive solid-phase extraction, Gas chromatography